Flywheel energy storage system based microgrid controller design and PHIL testing - Hiroshi Kikusato; Taha Selim Ustun; Masaichi Suzuki; Shuichi Sugahara; Jun Hashimoto; Kenji Otani; Nobuyoshi Ikeda; Iichiro Komuro; Hideaki Yokoi; Kunihiro Takahashi (Energy Reports, 2022)
Microgrids consisting of renewable energy based distributed generators have become popular as a way of energizing off-grid systems. Due to their low-inertia, these distributed generators require a robust frequency control system to maintain it. This problem is amplified by the fact that there is no centralized grid that anchor the system voltage and frequency. For this reason, such off-grid microgrid employs storage systems and diesel generators to provide some flexibility. Flywheel energy storage systems (FESSs) have very quick reaction time and can provide frequency support in case of deviations. To this end, this paper develops and presents a microgrid frequency control system with FESS. The system performance tests are performed with real-equipment where FESS is connected to digital real time simulator. Several frequency events are triggered and the frequency profile is observed to compare microgrid’s performance with and without the developed frequency control. Results show that flywheel energy storage system provides a much smoother frequency profile with less deviations.